2020
DOI: 10.1111/cfs.12774
|View full text |Cite
|
Sign up to set email alerts
|

‘The lion's den’: Social workers' understandings of risk to infants

Abstract: Recent research has highlighted the increasing trends in newborn and very young children entering child welfare processes and care proceedings in a number of countries. Furthermore, differential responses to risk within young families across different geographical locations and communities in the same child protection system have been found. Safe care arrangements for newborn babies may include placement with kinship carers or with foster carers not previously known to the family. The distinctive needs of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 26 publications
0
15
0
Order By: Relevance
“…Research shows that there are enduring psychological vulnerabilities for children adopted from care (e.g. Brown, Waters, & Shelton, 2017;Juffer & van Ijzendoorn, 2005) with evidence suggesting links with experiences of early adversity, such as toxicity in utero, birth complications, and early adverse childhood experiences (Tung, Christian-Brandt, Langley, & Waterman, 2020;Authors 2019;2020). However, few studies have examined the child characteristics and early environmental conditions associated with adopted children's development of post-traumatic stress (PTS) symptoms (Dovran, Winje, Arefjord, & Haugland, 2012), despite this group being more likely to be referred to Child and Adolescent Mental Health LATENT CLASS ANALYSIS OF PTS IN ADOPTED CHILDREN 4 Services (CAMHS) for specialist care (Trotter, 2017).…”
Section: Patterns Of Adversity and Post-traumatic Stress Among Childr...mentioning
confidence: 99%
“…Research shows that there are enduring psychological vulnerabilities for children adopted from care (e.g. Brown, Waters, & Shelton, 2017;Juffer & van Ijzendoorn, 2005) with evidence suggesting links with experiences of early adversity, such as toxicity in utero, birth complications, and early adverse childhood experiences (Tung, Christian-Brandt, Langley, & Waterman, 2020;Authors 2019;2020). However, few studies have examined the child characteristics and early environmental conditions associated with adopted children's development of post-traumatic stress (PTS) symptoms (Dovran, Winje, Arefjord, & Haugland, 2012), despite this group being more likely to be referred to Child and Adolescent Mental Health LATENT CLASS ANALYSIS OF PTS IN ADOPTED CHILDREN 4 Services (CAMHS) for specialist care (Trotter, 2017).…”
Section: Patterns Of Adversity and Post-traumatic Stress Among Childr...mentioning
confidence: 99%
“…As Ward et al (2006Ward et al ( , 2012's research has shown, infants considered at risk of significant harm in the English context are born into families experiencing multiple deprivations and difficulties, often over a long period. Nevertheless, the decision of whether to remove a baby soon after birth is a highly charged and difficult one for practitioners (Critchley, 2020a). Broadhurst et al (2017aBroadhurst et al ( , 2017b have explored in detail the significant short and long term impacts on birth mothers of infant removal, and particularly of repeat care proceedings leading to the removal of consecutive newborn babies from the same birth mother.…”
Section: Introductionmentioning
confidence: 99%
“…Continuity of care helps to reinforce relationships between professionals and pregnant women and allows for the development of trust and disclosure of sensitive issues (Oni et al, 2020). The importance of building good relationships with pregnant women to inform decision making was stressed by professionals in this study (Ayerle et al, 2012;Critchley, 2020). Adopting a non-judgemental, empathetic and compassionate approach towards pregnant women was paramount to inform and support the process of risk assessment (Reamer, 2013).…”
Section: Discussionmentioning
confidence: 96%